Decisional conflict and its determinants among patients with cancer undergoing immunotherapy combined with chemotherapy or targeted therapy: a cross-sectional study - Lee, Yun-Hsiang; Chou, Xiao-Yin; Lai, Yeur-Hur; Liang, Yi-Hsin; Hung, Chia-Tai; Hsaio, Chu-Chi; Gao, Zi-Xuan (Scientific reports, 2023)
Decisional conflict might occur during shared decision-making (SDM) because immunotherapy is a rather novel treatment option for patients with cancer. To explore the prevalence and severity of physical and psychological symptoms and the effort invested in SDM in relation to decisional conflict among patients with cancer undergoing immunotherapy combined with chemotherapy or targeted therapy. This was a cross-sectional survey study. The SURE version of the Decisional Conflict Scale was used to screen cancer patients’ decisional conflict status. Demographic or clinical characteristics, physical symptoms and psychological distress; efforts invested in the SDM process were also assessed as potential factors related to decisional conflict. One hundred seventeen patients surveyed, the prevalence of fatigue (79.5%), sleep disturbance (78.6%), poor appetite (67.5%), and pain (58.1%) symptoms were high and the severity was at moderate levels. The prevalence of pruritus (40.2%), rash (34.2%), dry skin (41.9%), and diarrhea (17.1%) symptoms were low and the severity was at mild levels. 65.8% of patients reported uncertainty, with mild to moderate levels. Furthermore, 97.4% of the patients made some effort in SDM, and the effort level was moderate (mean: 5.56 ± 2.02). 64.1% of patients were certain that immunotherapy was the best option. Age, uncertainty, and effort in the SDM process were major factors related to decisional conflict. We observed that older patients (age: ≥ 65) and those with higher uncertainty levels and less effort in SDM reported higher levels of decisional conflict. Future studies should explore older patients’ decisional related needs of immunotherapy. Interventions should be designed to reduce the uncertainty experienced by patients with cancer and enhance their understanding of immunotherapy to enable them to take more effort in the SDM process.